Effect of mechanical toothbrushing combined with different denture cleansers in reducing the viability of a multispecies biofilm on acrylic resins - Dias Panariello, Beatriz Helena [UNESP]; Izumida, Fernanda Emiko; Moffa, Eduardo Buozi; Pavarina, Ana Claudia [UNESP]; Jorge, Janaina Habib [UNESP]; Giampaolo, Eunice Teresinha [UNESP] (Mosher & Linder, Inc, 2016)
Purpose: To investigate the efficacy of immersion and brushing with different cleansing agents in reducing the viability of multispecies biofilm on acrylic resins. Methods: Lucitone 550 (L) and Tokuyama Rebase Fast II (T) specimens (10 x 2 mm) were prepared, sterilized, and inoculated with a suspension of Candida albicans, Candida glabrata, and Streptococcus mutans. Specimens were incubated for 48 hours at 37 degrees C for biofilm formation. Then, they were divided into groups (n=12) and subjected to brushing or immersion for 10 seconds in distilled water (W), 0.2% peracetic acid - Sterilife (Ac), 1% chlorhexidine digluconate (CHX), 1:1 water/dentifrice solution (D), 1% sodium hypochlorite (NaOCl), and sodium perborate/Corega Tabs (Pb). Viable microorganisms were evaluated by the XTT assay and colony counts (cfu/mL). Data were performed by ANOVA and Tukey test with 5% significance level. Results: The multispecies biofilm on L and T were killed by brushing or immersion in Ac, CHX, and NaOCl for only 10 seconds.